Проблеми капіталізації металургійних підприємств у сучасних умовах - Булєєв, І.П.; Солод, М.А. (Економіка промисловості, 2016)
Стаття присвячена проблемам капіталізації металургійного виробництва в умовах ускладнення ситуації на ринках металургійної продукції. На основі дослідження характерник провідних світових металургійних компаній, а також особливостей їх розвитку і стратегій визначено, що важливе місце серед стратегічних пріоритетів підприємств - світових лідерів посідають питання підвищення капіталізації, що має також стати одним з основних елементів планів модернізації вітчизняних підприємств металургійної галузі. Статья посвящена проблемам капитализации металлургического производства в условиях усложнения ситуации на рынках металлургической продукции. На основе исследования характерник ведущих мировых металлургических компаний, а также особенностей их развития и стратегий определенно, что важно место среди стратегических приоритетов предприятий - мировых лидеров занимают вопросы повышения капитализации, что должно также стать одним из основных элементов планов модернизации отечественных предприятий металлургической отрасли. The article is devoted to the investigation of the state and perspectives of capitalization of metallurgical production in contemporary conditions. The goal is to show that substantial worsening of socio-economic situation in the world and in the Ukraine leads to intensification of the problems inherent in the Ukrainian metallurgical enterprises, which requires additional efforts as to search and realize the new approaches adequate to the challenges of modern period. The research highlights that metallurgy today remains a foundation for development of leading industries of the world economy and it is a potential force cooperating the increase of competitiveness of domestic producers and the growth of national economy on the whole. The results of the analysis conducted show that, in spite of difficult situation, the metallurgical complex of Ukraine managed to remain in the ten of leading world producers. But without intensive modernization of heavily depreciated production facilities, minimization of negative environmental impact and long-awaited technology changeover, in the medium term perspective Ukrainian metal producers may loose their leadership due to inability to respond to further challenge concerning technological superiority of other global players. Domestic enterprises must be oriented to the leaders of the world metallurgical industry as to save and strengthen their positions. On the basis of the research of production descriptions and features of development and strategies of enterprises - world leaders of metallurgical production it is exposed that one of their main priorities is the issue of capitalization increase. The use of approaches approved by the world leaders of industry in the practice of domestic metallurgical enterprises not only will enable the promotion of efficiency of functioning and capitalization of national metallurgical production but also, as a result, will be instrumental in overcoming of the crisis phenomena and passing to steady development of national economy on the whole.